Identification of microRNAs as diagnostic biomarkers for atrial fibrillation: a systematic review and meta-analysis - Rizal, Ardian; Waranugraha, Yoga; Wikananda, Adhika Prastya; Yuniadi, Yoga (Frontiers in Cardiovascular Medicine, 2023)
Background. The genetic factors contribute to the AF pathophysiology by altering the structural and functional properties of proteins involved in different cellular activities. The m icroRNAs (miRNAs), which take part in structural and electrical remodeling during the AF evolution. The aim of study is to determine correlation between the expression of miRNAs and the development of AF, as well as to explain any potential importance of genetic factors in the AF diagnosis Methods and Results. Online scientific databases, including Cochrane, ProQuest, PubMed, and Web of Science were used to conduct the literature search. The keywords were associated with or characterized the relationship between miRNAs and AF. The pooled sensitivity and specificity statistical parameters were analyzed using a random-effects model. The miRNAs had a combined sensitivity and specificity of 0.80 (95% CI = 0.70 to 0.87) and 0.75 (95% CI = 0.64 to 0.83) for the diagnosis of AF, respectively. The area under the SROC was 0.84 (95% CI = 0.81 to 0.87). The DOR was 11.80 (95% CI = 6.79 to 20.50). This study also revealed that miRNAs had a pooled PLR of 3.16 (95% CI = 2.24 to 4.45) and NLR of 0.27 (95% CI = 0.18 to 0.39) for the diagnosis of AF. The miR-425-5p demonstrated the highest sensitivity (0.96, 95% CI 0.89-0.99) Conclusion. The meta-analysis revealed substantial connection between miRNA expression dysregulation and AF, supporting the potential diagnostic role of miRNAs. The miR-425-5p has potential role as a biomarker for AF.